The Role of E-administration in Narrowing the Gap between Parents and Schools - Al Noaim, Mansour (My University, 2019)
This research focuses on the role of electronic management system, Noor, and how to activate the communication process. This research shows previous studies in KSA mentioned that there is a lack of communication between the parents and schools. This research discussed how this study help to increase the rate of communication between parents and teachers by making the system easy to use and needing less effort. The study proposed to activate electronic messages through E-administration “Noor”. This research has suggested that developing Noor system and providing professional training for teachers and parents. It is expected that these new additions to Noor program will increase the rate of communication between teachers and parents
Keywords: Electronic Management; Digital Communication; Noor Program